Rekonstruksi, Keladillan, Pollil Rekonstruksi Keadilan Poligami Dalam Hukum Perkawinan Islam Di Indonesia : Rekonstruksi Keadilan Poligami Dalam Hukum Perkawinan Islam Di Indonesia - Mas adah, Mas adah; A'la, Abd (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2025)
Polygamy is a classic issue but is still interesting to study. The basis used is QS an Nisa verse 3. According to Musdah, this verse talks about how to provide protection for orphans. Even if polygamy is practiced, it is one breath with the protection of orphans. Therefore, the law of polygamy is haram lighayrih because the condition of its permissibility is justice which includes material and immaterial is very difficult to achieve. The prohibition of polygamy because of justice to his wives becomes the legal illat. The Marriage Law in Indonesia in regulating polygamy does not seem to be fair to women and views women as sub ordinate. While Musdah's thinking about polygamy in positive law in Indonesia is Article 3 paragraph (1) of Law No.1 of 1974 reads